AKULTURASI BUDAYA DALAM PEMBELAJARAN PAI - Azzahra Nabila Ramadhani; Ade Miftahul Irfan (JURNAL ILMIAH NUSANTARA, 2026)
Cultural acculturation refers to a dynamic process of interaction between Islamic values and local cultural traditions without eliminating the fundamental characteristics of each. In the context of Islamic Religious Education (IRE), cultural acculturation serves as a contextual learning approach that connects religious teachings with students’ social and cultural experiences. This article aims to examine the concept of cultural acculturation and its implementation in IRE learning as an effort to strengthen moderate and inclusive Islamic values. The research employs a library research method by analyzing relevant academic sources, including scholarly books, journal articles, and related documents. The findings indicate that integrating local cultural elements into IRE learning enhances religious understanding, fosters tolerance, and facilitates the internalization of Islamic values in students’ daily lives. Furthermore, cultural acculturation in IRE contributes to the development of students’ religious character, cultural awareness, and adaptability within a multicultural society. Therefore, cultural acculturation can be considered an effective learning strategy in Islamic Religious Education that aligns with contemporary socio-cultural developments.